Cinnamon essential oil and its emulsion as efficient antibiofilm agents to combat Acinetobacter baumannii - Ganić, Tea; Vuletić, Stefana; Nikolić, Biljana; Stevanović, Magdalena; Kuzmanović, Maja; Kekić, Dušan; Đurović, Saša; Cvetković, Stefana; Mitić-Ćulafić, Dragana (Frontiers in Microbiology, 2022)
Acinetobacter baumannii is an emerging nosocomial pathogen resistant to a wide spectrum of antibiotics, with great potential to form a biofilm, which further aggravates treatment of infections caused by it. Therefore, searching for new potent agents that are efficient against A. baumannii seems to be a necessity. One of them, which has already been proven to possess a wide spectrum of biological activities, including antimicrobial effect, is cinnamon essential oil. Still, further increase of antibacterial efficacy and improvement of bioavailability of cinnamon oil is possible by emulsification process. The aim of this study was comparative analysis of cinnamon essential oil and its emulsion against biofilm forming A. baumannii clinical isolates. Furthermore, the investigation of toxicological aspects of possible applications of essential oil and emulsion was done as well. Gas chromatography–mass spectrometry of essential oil indicated trans-cinnamaldehyde as the most abundant component. The cinnamon emulsion was synthesized from cinnamon essential oil by combining modified low- and high- energy methods. Synthesized emulsion was characterized with Fourier-transform infrared spectroscopy and photon correlation spectroscopy. Both substances exhibited significant antibacterial (minimal inhibitory concentrations in the range 0.125–0.5 mg/ml) and antibiofilm effects (inhibitions of formation and reduction of pre-formed biofilm were 47–81 and 30–62%, respectively). Compared to essential oil, the efficacy of emulsion was even stronger considering the small share of pure oil (20%) in the emulsion. The result of biofilm eradication assay was confirmed by scanning electron microscopy. Even though the cytotoxicity was high especially for the emulsion, genotoxicity was not determined. In conclusion, strong antibacterial/antibiofilm effect against A. baumannii of the cinnamon essential oil and the fact that emulsification even potentiated the activity, seems to be of great significance. Observed cytotoxicity implicated that further analysis is needed in order to clearly determine active principles being responsible for obtained antibacterial/antibiofilm and cytotoxic properties.